Revitalisasi Model Pengembangan Kurikulum Fakultas Ekonomi dan Bisnis Islam Berbasis Standar KKNI dan Islamic Entrepreneurship - Sugeng Riyadi; Badaruddin Badaruddin (el-Jizya : Jurnal Ekonomi Islam, 2018)
Curriculum is an important variable in education. To measure the success of education, standardization becomes one of important strategies in strata-ization of the alumni of a specific educational institution, in this case, Islamic Economics and Business Faculty. The policy transformation of Indonesian National Qualification Framework as inevitability of standardization group covers all higher educations including Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi. In this context, the mastery of knowledge and entrepreneurship practice that is inherent with the concept of Islamic theory (Islamic Entrepreneurship) is one of the primary indicators. From the field research that was conducted, descriptively, it can be identified that a serious legal revitalization effort can be the mainframe for operational activity in various Islamic Entrepereneur units in UIN Sulthan Thaha Saifuddin Jambi such as Mini Bank, Capital Market Galery and Business Incubation Center. This revitalization is elaborated in the implementation of Good Academic Governance in the faculty. The conclusions and suggestions arisen in a performance that is professional, transparent, and collective collegial for all institutional elements directly involved in the revitalization implementation of currciulum development model in Islamic Economics and Business Faculty of UIN Sultan Thaha Saifuddin Jambi based on Indonesian National Qualification Framework (INQF) standard result the alumni that have capability with Islamic Entrepreneurship character.